2016
DOI: 10.1007/s00259-016-3516-0
|View full text |Cite
|
Sign up to set email alerts
|

123I-mIBG scintigraphy in neuroblastoma: development of a SIOPEN semi-quantitative reporting ,method by an international panel

Abstract: PurposeA robust method is required to standardise objective reporting of diagnostic 123I-mIBG images in neuroblastoma. Prerequisites for an appropriate system are low inter- and intra-observer error and reproducibility across a broad disease spectrum. We present a new reporting method, developed and tested for SIOPEN by an international expert panel.MethodPatterns of abnormal skeletal 123I-mIBG uptake were defined and assigned numerical scores [0–6] based on disease extent within 12 body segments. Uptake inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 13 publications
(25 reference statements)
1
49
0
1
Order By: Relevance
“…A modified Curie scoring system also includes soft-tissue lesions and is currently widely used in multicenter trials conducted by a children's oncology group (31). A similar scoring system, proposed by the International Society of Paediatric Oncology Europe Neuroblastoma, uses a 0-6 grading scale for skeletal and soft-tissue disease (32) and is recommended by an international panel for universal routine evaluation of MIBG scanning in high-risk neuroblastoma patients (33). MIBG scoring has high prognostic value at diagnosis and is predictive of overall survival and event-free survival in high-risk and stage IV neuroblastoma after other systemic treatments and in assessment of disease before myeloablative therapy (34).…”
Section: I/ 131 I-mibg For Imaging Of Neuroblastomamentioning
confidence: 99%
“…A modified Curie scoring system also includes soft-tissue lesions and is currently widely used in multicenter trials conducted by a children's oncology group (31). A similar scoring system, proposed by the International Society of Paediatric Oncology Europe Neuroblastoma, uses a 0-6 grading scale for skeletal and soft-tissue disease (32) and is recommended by an international panel for universal routine evaluation of MIBG scanning in high-risk neuroblastoma patients (33). MIBG scoring has high prognostic value at diagnosis and is predictive of overall survival and event-free survival in high-risk and stage IV neuroblastoma after other systemic treatments and in assessment of disease before myeloablative therapy (34).…”
Section: I/ 131 I-mibg For Imaging Of Neuroblastomamentioning
confidence: 99%
“…The recent article in the journal by Professor Valerie Lewington and colleagues [1] on the semi-quantitative scoring of the burden of bone and bone marrow metastases by iodine-123 meta iodobenzylguanidine ( 123 I-mIBG) scans is a welcome addition to the literature on the imaging of children with neuroblastoma.…”
mentioning
confidence: 99%
“…In their recent paper, Lewington et al [1] have evaluated paired scans from diagnosis and after induction chemotherapy in 82 patients, of whom 62 had metastatic disease at presentation. With a response being defined as a 50% or greater reduction in the score, they found that those with the highest scores (>48/72) were significantly less likely to achieve a response to induction chemotherapy than those with lower scores at diagnosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations